Self-efficacy and Attitude of the Teachers of SMAN Kuansing District towards the Utilization of ICT - Hadriana Hadriana (Universitas Riau, 2019)
The development of Information and Communication Technology (ICT) has a very big influence on education. With the enactment of the 2013 Curriculum, a technology-based curriculum, teachers as learning agents must continue to equip themselves with knowledge related to ICT. This descriptive study aims to describe and analyze self-efficacy and attitudes of the teachers of SMAN Kuansing District towards the utilization of ICT in learning activities. Obstacles faced by the teachers in utilizing ICT and the efforts that have been done to overcome the obstacles are also discussed. The research data was collected in August 2018. By using stratified random sampling technique, 55 teachers were determined as the sample. The instrument used was a questionnaire. Then, the questionnaire was analyzed through descriptive statistics to obtain frequencies and percentages. Finally, it can be concluded that the average score of self-efficacy of the teachers of SMAN in Kuansing District in utilizing ICT is 80.6% and the average score of their attitudes is 92.8%. It means that their self-efficacy and attitude are in very good levels. Although there are many obstacles faced by teachers in terms of facilities, infrastructure and human resources, the teachers have their own strategies to solve those obstacle.